GC-MS Profiling and In Silico Antibacterial Activity of Strobilanthes tonkinensis Lindau Leaf Extracts via Maceration and Soxhlet Methods - Dwi Sapri Ramadhan; Dian Wardana; Hestia Hairima; Tita Juwitaningsih; Rosa Nadya Evelyn Sitorus; Vina Octavia Azzahra; Ilham Sinuraya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Strobilanthes tonkinensis Lindau (Acanthaceae; locally known as daun paris) is an aromatic medicinal herb of Southeast Asian origin whose extraction-method-dependent secondary metabolite composition and antibacterial potential against defined molecular targets have not been systematically characterized. This study profiled the GC-MS-detectable metabolome of four leaf extracts obtained by ethanol maceration of fresh (3×24 h) and dried leaves (3×24 h), ethanol Soxhlet (13 cycles, 6.5 h), and n-hexane Soxhlet (25 cycles, 10 h) extraction of dried leaves, identifying 19, 27, 12, and 7 compounds, respectively. Extraction method and solvent polarity strongly governed compound class distribution: fresh ethanol maceration was dominated by 2-propionyl-1,4,5,6-tetrahydropyridine (33.21%) and cis-vaccenic acid (14.63%), while n-hexane Soxhlet selectively enriched stigmasterol to 67.95% of total peak area approximately 19-fold higher than ethanol maceration (3.61%). Five representative metabolites, stigmasterol, phytol, lupeol, squalene, and 2-propionyl-1,4,5,6-tetrahydropyridine were subjected to molecular docking against FtsA (PDB: 3WT0), OmpF (PDB: 4KR4), and DNA gyrase B (PDB: 6KZV), with ADMET profiling performed via SwissADME and ProTox 3.0. Lupeol (-8.0 kcal/mol) and stigmasterol (-7.7 kcal/mol) surpassed the native OmpF ligand binding affinity and demonstrated strong interaction with DNA gyrase B, supporting multi-target antibacterial potential. Squalene showed preferential affinity for FtsA (-7.1 kcal/mol). Among the candidates, 2-propionyl-1,4,5,6-tetrahydropyridine was the sole Lipinski-compliant compound with high predicted oral absorption, all five metabolites displayed no predicted hepatotoxicity or carcinogenicity. These findings identify lupeol and stigmasterol as priority antibacterial leads from S. tonkinensis and establish n-hexane Soxhlet extraction as an effective strategy for targeted phytosterol enrichment from this species.